FAKTOR-FAKTOR YANG MEMENGARUHI PERUBAHAN ALOKASI BELANJA MODAL - Filma Ayu Dian Palupi (Jurnal Akuntansi, 2018)
The aim of this study is to examine and find scientific evidence about the impact into changing in original local government revenue, general allocation grant, special allocation fund, and unspent funds toward the changing in the allocation of capital expenditure on regencies in Indonesia. The sample of this study are the regencies in Indonesia taken by purposive sampling method. The analysis method that appropriate in this study is multiple linier regressions. The result of the data test proves that the changing of original local government revenue does not affect in the changing of capital expenditure allocation, the changing of general allocation grant negatively affected the changing of capital expenditure allocation, the changing of special allocation fund has positive effect to the changing of capital expenditure allocation, and the changing of unspent funds have positive effect to the changing of capital expenditure allocation. The conclusion of this study can be used as a reference in making a budget in order to achieve an effective and efficient budget, and can optimize the potential of the region, especially for public services. This study differs from prior research which using only local government budget changes in the same year without involving the realization.Keywords: Original Local Government Revenue, General Allocation Grant, Special Allocation Fund, unspent funds, and Capital Expenditure